Legal Counseling Regarding Juvenile Delinquency in Temiyang Village, Kroya District, Indramayu Regency - Dewinnisa; Didik Himmawan (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Juvenile delinquency is very rampant, especially among young people. What is currently rampant is brawls between students, free sex to underage pregnancy, alcohol and drugs. All of them need to be handled through socialization and counseling. In addition to counseling and socialization, the way to prevent juvenile delinquency in the current era of globalization is through good relationships between parents and children, good communication between the two. Because, the factor that children end up falling into the circle of delinquency is due to the lack of communication between parents and children. Lack of attention and affection from parents towards children. This counseling aims to ensure that Temiyang residents can understand the importance of educating and supervising their children in socializing, so that residents know that juvenile delinquency is an act that violates the law and is regulated by the Criminal Code and applicable legal regulations. From the results of the protest and pretest obtained during the implementation of the Legal Counseling event regarding Juvenile Delinquency on July 9, 2024 at the Temiyang Village Hall, it shows that the residents of Temiyang village are quite familiar with the rules and norms that apply in society. The villagers also admit that juvenile delinquency in their environment does not occur much, their children are also recognized as obedient and good children. But from several questions or input from residents, they as parents do not know how their children behave outside of supervision and outside the family environment.